2011
DOI: 10.1016/j.compedu.2010.07.011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of animation interactivity on novices’ learning of introductory statistics

Abstract: and their never-ending supports. This study was a one-way design where the independent variable was animation interactivity. In addition to a control group (Static Group) provided with only static materials, there were three groups with different levels of animation interactivity: 1) Animation with simple interactivity (Simple Animation Group), 2) animation with input vii manipulation (Input Group), and 3) animation with practice and feedback (Practice Group). A sample of 123 college students participated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 48 publications
1
53
0
1
Order By: Relevance
“…Gagne's taxonomy (1982) was mentioned by Rieber (1989Rieber ( , 1991, and Bloom's taxonomy (1956) was mentioned by Rigney (1976). Wang, Vaughn, and Liu (2011) referred to the revised taxonomy of Bloom (Anderson & Krathwohl, 2001). Recoding the initial learning outcomes with the BTr (Anderson & Krathwohl, 2001) has reduced the number of outcomes variates from 13 to 8, as can be seen in Table 1.…”
Section: Descriptive Resultsmentioning
confidence: 99%
“…Gagne's taxonomy (1982) was mentioned by Rieber (1989Rieber ( , 1991, and Bloom's taxonomy (1956) was mentioned by Rigney (1976). Wang, Vaughn, and Liu (2011) referred to the revised taxonomy of Bloom (Anderson & Krathwohl, 2001). Recoding the initial learning outcomes with the BTr (Anderson & Krathwohl, 2001) has reduced the number of outcomes variates from 13 to 8, as can be seen in Table 1.…”
Section: Descriptive Resultsmentioning
confidence: 99%
“…A C C E P T E D format size (e.g., Schnotz & Lowe, 2008), and level of interaction (e.g., Wang et al, 2011) can impact significantly on learning from visualizations. As such, biased comparisons that do not control these factors may lead to incorrect educational interpretations.…”
Section: Comparing Apples and Oranges? 18mentioning
confidence: 99%
“…However, a full interactive animation, which also included the primary interactions of dragging and controlling the topographic instrument, was the most effective. Similarly, in the study with engineers given a Lego truck to disassembly,Akinlofa et al (2013, see Section 3.2) observed that the most effective learning condition was the interactive virtual space, where participants could drag the computer replicas of the Lego This primary interactive display was a better instructional format than two simpler secondary interactive visualizations (static pictures and video), where the users could only change the presentations' pace.Because interactive features can help understanding STEM concepts (e.g.,Wang, Vaughn, & Liu, 2011; but seePedra, Mayer, & Albertin, 2015), they must be controlled in unbiased static versus animation comparisons. However, sometimes statics cannot include as many interactive facilities as animations (seeTversky et al, 2002), which may limit the scope of research that can be conducted linking interaction with presentation types.…”
mentioning
confidence: 99%
“…As a matter of fact, using animations has a significant impact on the students' understanding especially for sophisticated courses which need a tremendous amount of imagination by using basic animation techniques in PowerPoint presentations which provides an additional learning aid that support learning [1]. Moreover, it is suggested that increasing animation interactivity could significantly enhance students' achievement and improvement at the intermediate level of learning, in addition students confidence improvement and perception were not significantly impacted by the increase of animation interactivity [7]. It is well known that video tutorials are not a new concept [2] emerging in the late 1960s, since then, video modeling has been described as "instructional videos" or "video tutorials."…”
Section: Introductionmentioning
confidence: 99%